GAMBARAN PERILAKU REMAJA PENGGUNA ALAT ORTHODONTI DI DESA RANTAU SIALANG KECAMATAN KUANTAN MUDIK KABUPATEN KUANSING TAHUN 2017 - ravi ola; Yulda Ningsih (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2019)
Orthodonti is a branch specific in the profession of dentistry responsible study and supervise the growth of Growing Hibiscus relating structures, from birth to adulthood. In the village of Rantau Sialang in get data there are 45 teenagers who use orthodonti. Based on the results of interviews with 20 teenagers in Rantau Sialang Village note 14 teen people declared that they wear a tool for smoothing the teeth and orthodonti 6 others declared just follow the trend. The purpose of the research to know the description of the behavior of Teenagers In using of Orthodonti tools in the village of Rantau Sialang Kuantan Mudik Sub District Kuansing regency 2017. Type of this research is quantitative sampling technique with deskriftif saturated that is 45 of 45 respondents from the sample population. Results of research the majority of tool usage behavior orthodonti less well 27 (60%), age 21, namely 20-23 (46.7), gender female, namely 41 people (91.1%), high school education 25 people (55.5%), good knowledge of the respondents 28 people (62%), attitude negative 29 (64.4%). This research can add a better awareness in using of tools orthodonti for Teenage Users Tool Rantau Sialang to make it more seacoast cleanliness or health in using of tools orthodonti.